Structural Elements and Neotectonics of Prince Edward County, Southern Ontario - McFall, Gail (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTThe seismically active Clarendon-Linden Fault of western New York State appears to connect with the Salmon River Fault and possibly with the Picton Fault, both of which cut through Prince Edward County, southern Ontario. Bedrock exposures display a variety of structural features including faults, fractures, and pop-ups which indicate that the region has been subjected to repeated tectonism since the Middle Ordovician. Thus, despite the general perception that Prince Edward County and the rest of the Lake Ontario region is one of low seismic potential, geological and geophysical data suggest otherwise.